The Relationship Between Level of Health Knowledge and use of Herbal Therapy for Hypertension Patients at Aldehia ( One-Sere, Casmuto, Suli-Ua) Suco Buruma, Posto Administrativo Baucau, Municipiu Baucau, Timor Leste - Novio De Almeida Pareira; Christina Trisnawati Setiawan; Maria Goreti Owa; Carmelita Barros; Yoseph Uliyanto; Leny Blegur (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
This study aims to analyse the relationship between the level of health knowledge and the use of herbal therapy in hypertensive patients in Aldehia (One-Sere, Casmuto, Suli-Ua), Suco Buruma, Posto Administrativo Baucau, Municipiu Baucau, Timor Leste in 2024. This study used a quantitative design with a cross-sectional approach. The study population consisted of hypertensive patients in Aldehia (One-Sere, Casmuto, Suli-Ua), Suco Buruma, Posto Administrativo Baucau, Municipiu Baucau, Timor Leste in 2024. The sample was selected by random sampling. Data were collected through a structured questionnaire with variables of health knowledge, use of herbal therapy, and other factors that influence the decision to use herbal therapy.65% of hypertensive patients have a low level of health knowledge and 67.5% do not use herbal therapy. There was a significant relationship between the level of health knowledge and the use of herbal therapy. Statistical tests showed that a better level of health knowledge tended to be associated with increased use of herbal therapy, with a significant p-value (p = 0.000), which suggests that health knowledge influences patients' decision to adopt herbal therapy. Education level was significantly associated with herbal therapy use (p = 0.015), where higher education level increased the likelihood of herbal therapy use (Exp(B) = 2.034). This study shows the importance of improving health knowledge and education in influencing the use of herbal therapy among hypertensive patients.